TARGET SPECIFIC LARVICIDAL EFFECT OF CAPPARIS ZEYLANICA L. (CAPPARACEAE) FOLIAGES AGAINST FILARIAL VECTOR CULEX QUINQUEFASCIATUS SAY (1823) - ANUSHREE SINGHA RAY; KUNTAL BHATTACHARYA; GOUTAM CHANDRA (International Journal of Pharma and Bio Sciences, 2015)
After prolonged use of the synthetic insecticides, novel insecticides of botanical origin are preferred for environment safety as well as human life. Present study was conducted to evaluate the larvicidal capability of Capparis zeylanica against Culex quinquefasciatus. Crude, cold and hot aqueous and ethyl acetate solvent extracts of foliages of C. zeylanica were tested against all instars larvae of Cx. quinquefasciatus. Lethal concentrations were determined. Effect on the non target water fauna was also tested. Cent percent mortality was found with 0.25% concentration of crude extracts against 1st and 2nd instar larvae. No larvicidal responses were found with cold and hot aqueous extracts. Highest mortality was found against 1st and 2nd instar larvae at 90 ppm concentration of ethyl acetate extracts at 72 h post exposure. Non-target populations were found non-responsive to active fraction. Secondary metabolites like Tannin, flavonoids and terpenoid were detected through preliminary qualitative phytochemical tests.